UNDERGRADUATE DENTAL STUDENTS’ AND INSTRUCTORS’ PERCEPTIONS ABOUT THE QUALITY OF CLINICAL FEEDBACK - Javed, Muhammad Qasim; ahmed, Alia; habib, Rashid (Journal of Ayub Medical College Abbottabad, 2021)
Background: Feedback is an essential component of the clinical skills development of dental students. The clinical training is a complex integration of knowledge, psychomotor skills, behaviour and clinical communication skills under stress for both instructor and student. This study aimed to investigate the perceptions of undergraduate dental students and their instructors on the quality of clinical feedback. Methods: The current cross-sectional observational study was conducted at the Department of Operative Dentistry and Endodontics, Riphah International University, Islamabad from August to December 2019. A self-administered questionnaire was used to collect responses from final year undergraduate dental students and faculty. The questionnaire comprised of 13 items, subdivided into six categories, targeting the various aspects of clinical feedback. SPSS 23 was utilized to analyse the data. Descriptive statistics were tabulated and data was analysed using the Mann-Whitney test (p<0.05) for differences between the two cohorts. Results: The mean age of the 64 students who responded was 24±0.8 years. Students’ male to female ratio was 1:1.56, while for the 18 instructors the ratio was 1:1. Good agreement between the students and instructors was shown for items related to personal dignity and empathy. Moderate agreement was found for items covering the domains of time, understanding, comfort level, professionalism, and self-assessment. The disagreement was observed for the items associated with conflicting feedback, conflict satisfaction, and effective communication. Conclusion: Incongruousness existed between the dental students and instructors, about the quality of clinical feedback provided to the dental students. Communication between the instructors and learners must be promoted to increase the level of understanding of the feedback given by the clinical instructors. Keywords: Dental education; Dental students; Feedback; Clinical clerkship